Exploring display techniques for mobile collaborative learning in developing regions - Jain, Mohit; Birnholtz, Jeremy; Cutrell, Ed; Balakrishnan, Ravin (MobileHCI 2011: Proceedings of the 13th International Conference on Human Computer Interaction with Mobile Devices and Services, 2011)
The developing world faces infrastructural challenges in providing Western-style educational computing technologies, but on the other hand observes very high cell phone penetration. However, the use of mobile technology has not been extensively explored in the context of collaborative learning. New projection and display technologies for mobile devices raise the important question of whether to use single or multiple displays in these environments. In this paper, we explore two mobile-based techniques for using co-located collaborative game-play to supplement ESL (English as a Second Language) education in a developing region: (1) Mobile Single Display Groupware: a pico-projector connected to a cell phone, with a handheld controller for each child to interact, and (2) Mobile Multiple Display Groupware: a phone for each child. We explore the types of interaction that occur in both of these conditions and the impact on learning outcomes.